2020
DOI: 10.1002/nop2.739
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among frail older persons (65+ years) in nursing homes: A cross‐sectional study

Abstract: Aim To assess the quality of life in frail older persons (65+ years) living in nursing homes and to examine differences between quality of life perceptions among different gender and age groups. Design Cross‐sectional. Methods Data were collected during 2015‐2017 based on two questionnaires (WHOQOL‐OLD and WHOQOL‐BREF). Seventy‐eight older persons living in nursing homes in southern Sweden answered the questionnaires in structured interviews. Descriptive and comparative statistics were used to analyse the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
1
9
2
Order By: Relevance
“…While Sandgren, Arnoldsson [32] found no differences in QoL between gender and age groups, female gender was associated with higher perceived Intimacy, and younger age seemed to be associated with better Sensory Abilities in this study. Another study equally reported higher scores in Intimacy for female participants but better Sensory Abilities with increasing age [34], even though this study was not conducted in long-term care homes.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…While Sandgren, Arnoldsson [32] found no differences in QoL between gender and age groups, female gender was associated with higher perceived Intimacy, and younger age seemed to be associated with better Sensory Abilities in this study. Another study equally reported higher scores in Intimacy for female participants but better Sensory Abilities with increasing age [34], even though this study was not conducted in long-term care homes.…”
Section: Discussioncontrasting
confidence: 83%
“…Yet, participants in our study reported higher QoL in the scale of Death or Dying compared to previous research [ 26 , 31 ], with participants in this study being less concerned about their own death. Another study assessing QoL in people living in long-term care homes also found the highest values for Death and Dying [ 32 ]. Yet, the WHOQOL-OLD is validated for community-dwelling older individuals and thus, the differences to the validation study by Power, Quinn [ 26 ] are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found in the facet death and dying the lowest overall average, of 14.33 (71.6%), which reduced the QOL, although it still qualified as regular, converging with other studies(Billett et al, 2019 ; Scherrer Júnior et al, 2020 ) where this relationship with death and dying is satisfactory, including a study carried out in support homes in Switzerland, where the results showed that fragile elderly have little or no fear of dying (Sandgren et al, 2020 ). This data differs from a study carried out in Santa Catarina / Brazil with 122 elderly, with incomplete primary education and a total QOL score of around 50%, with facet death and dying being the lowest score(Gato et al, 2018 ).…”
Section: Discussionsupporting
confidence: 75%
“…Older persons’ psychological quality of life often decreases due to low autonomy related to few opportunities to engage in everyday activities, being unable to do things they used to do, and not feeling in control of their future. 53 This signals that psychological care actions require attention. With communications training for CNs, older persons’ psychological wellbeing may increase.…”
Section: Discussionmentioning
confidence: 99%